Lembaga Negara Independen Di Indonesia Dalam Perspektif Konsep Independent Regulatory Agencies - Rizki Ramadani (Jurnal Hukum IUS QUIA IUSTUM, 2020)
This study aims to determine the independency of Independent State Institutions (LNI) in Indonesia with the perspective of the concept of Independent Regulatory Agencies (IRAs). In addition, it also analyzes the LNI model that is in line with the concept of IRAs. The number of Independent State Institutions (LNI) in Indonesia has relatively increased since the amendment of the 1945 Constitution. However, the need for institutions that are free from government interference is not accompanied by the formulation of standards and mature institutional design on the aspect of independence as the main characteristic of LNI. This study uses a normative method, with statutory and conceptual approaches. This study concludes that the independence of LNI in Indonesia tends to be non-uniformed. Some institutions meet the aspects of formal independence in the concept of IRAs, but some others still have aspects of regulation that are incomplete. The results of the study of de facto independence also concluded that there were interventions, politicization and resistance from various parties towards the presence and policy of LNI in Indonesia. The LNI model that is in line with the IRAs concept can be done by improving 3 aspects: first, minimizing the authority of the DPR in the selection of LNI leaders, second, providing independent authority, and third, emphasizing the non-partisan provisions in each institutional regulation of LNI.